Methoxychlor exposure induces oxidative stress and affects mouse oocyte meiotic maturation. Issue 9 (2nd September 2016) - Liu, Yu; Wang, Ya‐Long; Chen, Ming‐Huang; Zhang, Zhen; Xu, Bai‐Hui; Liu, Rui; Xu, Lin; He, Shu‐Wen; Li, Fei‐Ping; Qi, Zhong‐Quan; Wang, Hai‐Long
SUMMARY: Methoxychlor (MXC) is used worldwide against insects and other pests. This organochlorine pesticide acts as a xenoestrogen, promotes oxidative stress, and is considered cytotoxic and genotoxic, causing abortions and stillbirths in females. Mechanistically related estrogens and oxidants affect oocyte meiosis, so we investigated the effects of MXC on mouse oocyte meiotic maturation. Our results showed that maturation rates of MXC‐treated oocytes were lower than those of controls, which was due to abnormal spindle morphologies and DNA double‐strand breaks, as confirmed by increased γ‐H2AX foci. Our findings also suggest that MXC may affect oocyte quality by causing the accumulation of superoxide radicals and other reactive oxygen species, aberrant mitochondrial distribution, decreased mitochondrial membrane potential, and increased lipid peroxidation. Thus, exposure to MXC negatively affects oocyte meiotic maturation, primarily through impairments in cellular ROS metabolism. Mol. Reprod. Dev. 83: 768–779, 2016 © 2016 Wiley Periodicals, Inc .